Temporal dynamics of the urban heat island of Singapore - CHOW, Winston T. L. (Institutional Knowledge at Singapore Management University, 2006)
The temporal variability of the canopy‐level urban heat island (UHI) of Singapore is examined for different temporal scales on the basis of observations during a 1‐year period. Temperature data obtained from different urban areas (commercial, Central Business District (CBD), high‐rise and low‐rise housing) are compared with ‘rural’ reference data and analysed with respect to meteorological variables and differences in land use. The results indicate that the peak UHI magnitude occurs 3–4 h (>6 h) after sunset in the commercial area, (at other urban sites). Higher UHI intensities generally occur during the southwest monsoon period of May–August, with a maximum of ∼7 °C observed in the commercial area under ideal meteorological conditions. Variations in seasonal precipitation explain some of the differences in urban–rural cooling. No clear relationship between urban geometry and UHI intensity can be seen, and intra‐urban variations of temperature are also shown to be influenced by other site factors, e.g. the extent of green space and anthropogenic heat. Lastly, results from the present study are compared with UHI data from other tropical and mid‐latitude cities.